PENGARUH PENGUNGKAPAN SUSTAINABILITY REPORT TERHADAP KINERJA DAN NILAI PERUSAHAAN - Bima Putranto Sejati; Andri Prastiwi (Diponegoro Journal of Accounting, 2015)
Environmental damage becomes seriously problem in this decade and the most damagerrefers to companies. One of their responsibility is publish their Sustainability Report. Sustainability Report helps companies to show their responsibility about the Economy, Social and Environment aspects. Sustainability Report Disclosure follows the guidelines from Global Reporting Initiative (GRI), G3 and G3.1, both consist of three main aspects which are Economic performance, Environment performance and Social performance. In this research, the data population taken from companies that publishes Sustainability Report and listed into Indonesia Stock Exchange starts from 2006 – 2013. The result of this research shows that Sustainability Report Disclosure does not have any significant relation on firm performance and firm value. Then, the disclosure of Economy Performance, Environment Performance and Social Performance of Sustainability Report also does not have significant relation on firm performance and firm value